Cesar Vallejo: for education in our lives - Cardona López, José (Espergesia, 2015)
Beginning with four poems from the book Human Poems, in this article it is stated that in the poetic work of Vallejo there is also a script that moves on while denying the word itself. In the exposition, it is argued that the poet would propose to bear in mind another aspect in the education of our lives i.e. to know that silence is part of our protests before the abuses of the absurdities and ironies of society, to know that silence is also outcry. Likewise, silence is also the right to be exercised before the sorrows and other inconveniences posed to live our lives in society.